The concept of cleanliness in the Hebrew Bible - Rashid, Ungaran (2021)
Cleanliness is a part of human life because cleanliness reflects a person's character. Cleanliness can be seen from the state of being clean and the habit of pursuing and maintaining cleanliness. This article examines the concept of cleanliness from the perspective of the Hebrew Bible, which discussed as a comparison of the same idea from the Quranic perspective that is written in another chapter of this book. In the Hebrew Bible, the concept of cleanliness includes two aspects, namely spiritual and physical. These two aspects are related to one another in terms of interaction, either interaction between human and God, human and other humans, human and nature, and human with him/herself. The discussion of cleanliness from a biblical perspective is by exegeses from the Hebrew Bible.